2004
DOI: 10.1177/0091270004264641
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Safety Evaluation of Palonosetron, a 5‐Hydroxytryptamine‐3 Receptor Antagonist, in U.S. and Japanese Healthy Subjects

Abstract: Palonosetron (Aloxi, Onicit) is a selective 5-HT(3) receptor antagonist recently approved by the Food and Drug Administration for the prevention of acute and delayed chemotherapy-induced nausea and vomiting. This study was performed to determine the pharmacokinetics and assess the safety and tolerability of intravenous (IV) palonosetron in healthy U.S. and Japanese subjects. Subjects were administered a single IV dose of palonosetron, ranging from 0.3 to 90 microg/kg in either of two randomized, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 12 publications
6
106
1
2
Order By: Relevance
“…[13][14][15][16][17] Palonosetron may also have other advantages for perioperative care. For example, a recent study reported by Cho et al 34 found that palonosetron 0.075 mg iv administered before induction of anesthesia reduced injection pain associated with rocuronium administration; the NNT was 2.94.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17] Palonosetron may also have other advantages for perioperative care. For example, a recent study reported by Cho et al 34 found that palonosetron 0.075 mg iv administered before induction of anesthesia reduced injection pain associated with rocuronium administration; the NNT was 2.94.…”
Section: Discussionmentioning
confidence: 99%
“…Méthodes Nous avons effectué une recherche systématique dans les bases de données MEDLINE Ò , EMBASE TM , le Registre central Cochrane des essais cliniques contrô lés et Web of Science Ò pour identifier les essais randomisés contrô lés qui ont abordé la comparaison de l'efficacité antiémétique dans les 24 premières heures suivant une chirurgie, du palonosétron et de l'ondansétron administrés à titre prophylactique. Les principaux critères d'évaluation étaient le pourcentage de participants éprouvant des nausées postopératoires (NPO), des vomissements postopératoires (VPO) ou les deux, dans la période précoce (0-6 heures) ou tardive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Postoperative nausea and vomiting (PONV), the big ''little problem'', 1 is the most common postoperative medical problem. From the perspective of both patients and healthcare providers, prophylaxis of PONV is equally as important as postoperative analgesia.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…The antiemetic ability of the medication is achieved through the inhibition of 5-HT3 receptors involving both medullary chemoreceptor zone and GI tract. 9 This inhibition of 5-HT3 receptors, thus represses the visceral afferent acceleration of the vomiting focus likely in a roundabout way at the level of the region postrema and in addition through direct restraint of serotonin activity inside the zone of postrema and the chemoreceptor trigger zone. 10 Alternate mechanism seems to basically responsible for emetogenic chemotherapy-induced nausea and vomiting, since comparable temporal relationship have not been documented between serotonin and emesis caused beyond first day after a dose and these agents are generally not sole responsible in preventing or alleviating the delayed effect.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-hydroxytryptamine-3 (5-HT3) receptor antagonists are popular drugs for PONV prophylaxis because of their similar efficacy to droperidol or dexamethasone and their favourable side-effect profile.2 Palonosetron is a new, potent, selective 5-HT3receptor antagonist with a strong receptorbinding affinity and a long elimination halflife and, therefore, a long duration of efficacy [10], [11] .…”
Section: Introductionmentioning
confidence: 99%